2018
DOI: 10.3389/fnins.2018.00975
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Disturbances of the Amplitude of Low-Frequency Fluctuations (ALFF) and Fractional ALFF in Alzheimer Spectrum

Abstract: Background: Alzheimer’s disease (AD) is a common neurodegenerative disease in which the brain undergoes alterations for decades before symptoms become obvious. Subjective cognitive decline (SCD) have self-complain of persistent decline in cognitive function especially in memory but perform normally on standard neuropsychological tests. SCD with the presence of AD pathology is the transitional stage 2 of Alzheimer’s continuum, earlier than the prodromal stage, mild cognitive impairment (MCI), which seems to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
156
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(179 citation statements)
references
References 75 publications
9
156
0
2
Order By: Relevance
“…The robustness of the results was tested to prove the regions we found was stability and repeatability ( Supplementary Figures S2, S3). In the studies pretend to explore the neural mechanism about MCI, AD or depression, these regions also have been mentioned (Langenecker et al, 2007; Alexopoulos et al, 2008;Yao et al, 2009;Lee et al, 2012;Xie et al, 2012;Zhang et al, 2012;Rizio and Dennis, 2014;Guo et al, 2016;Stoyanov et al, 2017;Kandilarova et al, 2018;Yang et al, 2018;Kandilarova et al, 2019). These brain regions may be the proof of a possible shared pathophysiology in both depression and MCI (Yao et al, 2009;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The robustness of the results was tested to prove the regions we found was stability and repeatability ( Supplementary Figures S2, S3). In the studies pretend to explore the neural mechanism about MCI, AD or depression, these regions also have been mentioned (Langenecker et al, 2007; Alexopoulos et al, 2008;Yao et al, 2009;Lee et al, 2012;Xie et al, 2012;Zhang et al, 2012;Rizio and Dennis, 2014;Guo et al, 2016;Stoyanov et al, 2017;Kandilarova et al, 2018;Yang et al, 2018;Kandilarova et al, 2019). These brain regions may be the proof of a possible shared pathophysiology in both depression and MCI (Yao et al, 2009;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…IBA involves dynamic neural and metabolic activities, it is activity and plays a pivotal role in brain function (Dai and He, 2014;Raichle, 2015). These methods have been widely used to evaluate the IBA of neurological disorders or neuropsychiatric disorders, such as AD, depression, and MCI (Yao et al, 2009;Zhang et al, 2012;Guo et al, 2016;Wee et al, 2016;Stoyanov et al, 2017;Zhang et al, 2017;Kandilarova et al, 2018;Yang et al, 2018;Liu et al, 2019). Furthermore, evidence indicated that once brain got an internal or external stimuli, it could respond by dynamic integration or adjustment over multiple time scales (Hutchison et al, 2013;Bassett and Sporns, 2017;Yan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, aMCI group showed more widespread topological changes involving the frontal lobes (Barban et al, 2017), and aberrant connectivity was also found in patients with SCD between DMN and FG due to cognitive impairment (Xue et al, 2019). Besides, an increasing trend of values of amplitude of low-frequency fluctuation (ALFF) and fractional ALFF were detected in FG (Yang et al, 2018). Therefore, changes in FG may be related to cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 91%
“…Anatomically, it includes the anterior DMN (aDMN) which is primarily composed of the ventromedial prefrontal cortex (vmPFC), and posterior DMN (pDMN) which mainly focuses on the posterior cingulate cortex (PCC) (Xu et al, 2016). Notice that the former mainly concerns memory extinction and self-referential mental idealization, while the latter is closely related to the function of episodic memory retrieval (Yang et al, 2017(Yang et al, , 2018. Previously, it has been reported that amyloid deposits are detected with a great probability in the PCC which served as a primary part of DMN (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%